Productive Zakat Based on Local Potential: A Multi-Case Study in Rural and Urban Areas - Ekaviana, Dessy; Nur Ramadhani, Febrina (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This study explores the implementation of locally-based productive zakat programs in urban and rural contexts, aiming to analyze the effectiveness of integrating local economic potential in empowering zakat beneficiaries. Using a qualitative multi-case study approach, Wahdah Inspirasi Zakat (WIZ) Makassar was selected as the urban case and LAZISMU Grobogan as the rural case. Methods: Data were collected through in-depth interviews and document analysis. Results: The results reveal that leveraging local potential in productive zakat programs significantly improves the income and economic independence of mustahik. WIZ Makassar focuses on skills training, micro-business support, and women empowerment to address urban poverty. In contrast, LAZISMU Grobogan utilizes rural resources such as goat farming and organic fertilizer production to support small businesses and community welfare. The study identifies five key phases in program success: mapping potential, selecting beneficiaries, providing continuous assistance, monitoring business progress, and conducting evaluation. Conclusion and Suggestion: However, challenges persist, including beneficiaries' preference for consumptive aid and the limited human resources in zakat institutions. To overcome these barriers, strategies such as community education, institutional capacity development, and funding diversification are necessary. The findings underscore the importance of context-specific zakat management models tailored to local characteristics, ensuring sustainable economic empowerment. This research offers a practical framework for zakat institutions seeking to optimize the impact of productive zakat programs in varied socioeconomic settings.